1980
DOI: 10.5636/jgg.32.567
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of pillow basalt from the Kinan seamount chain, the Shikoku Basin.

Abstract: Tholeiitic pillow basalt dredged from the Hakuho seamount located in the Kinan seamount chain, the Shikoku Basin, has peculiar magnetic properties; wide range intensity and high stability of natural remanent magnetization (NRM), low susceptibility, high initial Curie temperature and relatively small lattice constant. Four specimens of the pillow basalt have been cored from rim to center of one boulder sample. The NRM intensity decreases from center to rim, but the stability increases from center to rim. Reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The 15 km isodepth curve of the Philippine Sea Plate in the study area almost coincides with the 300°C isothermal line (Figure 4b) [ Higashikata et al , 2001]. It is possible to explain the observed reduction in magnetization as the temperature effect if a main magnetic carrier of the oceanic basalt is titanomagnetites, which has Curie temperatures between ∼150° and 250°C [ Furuta et al , 1980; Furuta , 1993]. However, the thermal condition based on heat flow observations shows no significant differences between AS and KP (Figure 4b) although they are a pair of back‐arc basin flanks.…”
Section: Discussionmentioning
confidence: 80%
“…The 15 km isodepth curve of the Philippine Sea Plate in the study area almost coincides with the 300°C isothermal line (Figure 4b) [ Higashikata et al , 2001]. It is possible to explain the observed reduction in magnetization as the temperature effect if a main magnetic carrier of the oceanic basalt is titanomagnetites, which has Curie temperatures between ∼150° and 250°C [ Furuta et al , 1980; Furuta , 1993]. However, the thermal condition based on heat flow observations shows no significant differences between AS and KP (Figure 4b) although they are a pair of back‐arc basin flanks.…”
Section: Discussionmentioning
confidence: 80%
“…The three basic approaches to sampling have been dredging (e.g., Merrill and Burns, 1972;Furuta et al, 1980;Gee et al, 1988), drilling (Marshall, 1978;Rice et al, 1980;, and studying subaerially exposed sections on oceanic islands (Gee et al, 1989). In general, these studies have shown that seamount magnetic properties not only differ from those found in "typical" seafloor basalts but are highly variable both within and among seamounts.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of numerous studies on magnetization of seamounts from magnetic anomalies (e.g., Sager and Pringle, 1988;, the magnetic structure of seamounts is still unclear. Previous paleomagnetic studies on dredged and drilled samples from seamounts and islands show that the magnetic properties of seamount rocks are highly variable (Furuta et al, 1980;Kono, 1980;Gee et al, 1988Gee et al, , 1989. Gee et al (1989) suggest that induced magnetization significantly contributes to seamount magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Sager and Pringle (1988) suggest that the magnitude of seamount magnetization derived from the seamount magnetic anomaly is almost the same as that obtained from dredged samples and that the induced magnetization of seamounts is negligible. Pillow basalts dredged from seamounts show high Q ratios (Furuta et al, 1980;Gee et al, 1988).…”
Section: Introductionmentioning
confidence: 99%